FLOOD MODEL SIMULATION OF PURNAMA STREET AREA DUE TO INCREASE OF WATER LEVELS OF THE KAPUAS RIVER AND THE INTENSITY AND DURATION OF RAIN - Fakhrully, Ya' Dhally; Umar, Umar; Gunarto, Danang; Herawati, Henny; Yulianto, Eko (Jurnal Teknik Sipil, 2022)
Flooding is a condition where water is not accommodated or the flow of water is obstructed in the sewer, so that it overflows to inundate the surrounding area. The area around the ditch on Purnama Street (the estuary of the Kapuas River) is affected by tides and the intensity and duration of rainfall. This study aims to simulate the flood model that occurred in the Purnama Street area. Data analysis was carried out using HEC-RAS software as a tool for modeling drainage flow. The research was conducted during no rain conditions, 5 and 10 year return periods of rain and the highest and lowest tidal conditions. The flood model simulations were carried out from Demang Ditch to the Lower Kapuas River. The results of the modeling using HEC-RAS show that the drainage channel from the Kapuas River to Purnama Street does not experience inundation/flooding, but in the area of Purnama Street to Demang Ditch during the 5 and 10 year return period rains and the highest tides experience inundation/flooding. which reaches the highway.